Uporaba ortoz in funkcionalne električne stimulacije v domačem okolju pri pacientih z okvaro hrbtenjače - Tkalec, Jana (Rehabilitacija (Ljubljana), 2024)
Background: The upright position in patients with spinal cord injury improves their psychological status, renal function, bone density, positively affects spasticity, orthostatic hypotension and joint range of motion. Various assistive devices can be used for standing and walking, such as knee ankle foot orthoses and functional electrical stimulation (FES). The aim of the research was to find out how people with spinal cord impairment use these aids in their home environment, what is their impact on functional abilities, quality of life and positive effects and possible negative experiences when using them. Methods: The survey was sent to 139 patients with spinal cord injury, who completed rehabilitation at the University Rehabilitation Institute, Republic of Slovenia (URI) from 2013 to 2017, and received orthoses or FES for one or both lower limbs at the time of dismissal. Research was approved by the Medical Ethics Committee of the URI (No. 61/2018). Results: Of the 98 patients who received orthoses, 45 returned the completed survey. Of these, the majority (87 %) still use the orthoses, mostly for walking outside (41 %). Among the positive effects, better well-being (69%) was most often mentioned, while the unwanted features were the difficult and long-lasting installation of orthoses (36 %). Of the 41 patients who received FES, we received 18 completed surveys. Even oBackground: The upright position in patients with spinal cord injury improves their psychological status, renal function, bone density, positively affects spasticity, orthostatic hypotension and joint range of motion. Various assistive devices can be used for standing and walking, such as knee ankle foot orthoses and functional electrical stimulation (FES). The aim of the research was to find out how people with spinal cord impairment use these aids in their home environment, what is their impact on functional abilities, quality of life and positive effects and possible negative experiences when using them. Methods: The survey was sent to 139 patients with spinal cord injury, who completed rehabilitation at the University Rehabilitation Institute, Republic of Slovenia (URI) from 2013 to 2017, and received orthoses or FES for one or both lower limbs at the time of dismissal. Research was approved by the Medical Ethics Committee of the URI (No. 61/2018). Results: Of the 98 patients who received orthoses, 45 returned the completed survey. Of these, the majority (87 %) still use the orthoses, mostly for walking outside (41 %). Among the positive effects, better well-being (69%) was most often mentioned, while the unwanted features were the difficult and long-lasting installation of orthoses (36 %). Of the 41 patients who received FES, we received 18 completed surveys. Even of these, the majority (83f these, the majority (83 %) still use FES, mostly for outdoor walking (47 %) and muscle strengthening (27 %). Among positive effects, improved quality of life was most often mentioned (53 %), while fear of falling (47 %) was the most frequently listed problem with the use of FES. Conclusions: Most patients still use the prescribed device because of various positive effects on their well-being and quality of life.
Keywords: Electric Stimulation; functional electrical stimulation; funkcionalna električna stimulacija; okvara hrbtenjače; Orthotic Devices; orthotics; ortoze; positive effects; pozitivni učinki; rehabilitation; Spinal Cord Injuries; spinal cord injury